2019
DOI: 10.21098/jimf.v5i3.1154
|View full text |Cite
|
Sign up to set email alerts
|

Financial and Social Efficiency on Indonesian Islamic Banks

Abstract: This paper explores financial and social efficiency in one assessment framework. Inorder to measure efficiency level of Islamic Banking Industry, this study uses DataEnvelopment Analysis (DEA) and Free Disposal Hull (FDH) methods. The resultsshow that the level of financial efficiency of Islamic banks in Indonesia from 2013 to2018 tends to decrease. On the contrary, the level of social efficiency of Islamic banksin Indonesia has a tendency to increase. Furthermore, the value of social efficiency ofIslamic bank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Namun demikian hal ini merupakan terobosan baru, relatif jika dibandingkan dengan penelitian-penelitian lainnya yang ada di dalam sampel penelitian ini. Rusydiana & Marlina (2019) telah juga mem-propose istilah baru yaitu social efficiency, dimana dalam hal ini perbedaannya terletak pada pemilihan variabel output yang mengarah ke arah aktivitas sosial, yaitu pembiayaan (financing) ke usaha kecil (small business) dan dana sosial (social fund). Mereka melakukan pemilihan variabel untuk social efficiency tersebut dengan merujuk dan memodifikasi dari paper penelitian Widiarto & Emrouznejad (2015) dan (Gutierrez-Goiria, San-Jose, & Retolaza, 2016) yang meneliti tentang social efficiency pada lembaga keuangan Microfinance.…”
Section: Gambar 2 Proporsi Pemilihan Objek Penelitianunclassified
“…Namun demikian hal ini merupakan terobosan baru, relatif jika dibandingkan dengan penelitian-penelitian lainnya yang ada di dalam sampel penelitian ini. Rusydiana & Marlina (2019) telah juga mem-propose istilah baru yaitu social efficiency, dimana dalam hal ini perbedaannya terletak pada pemilihan variabel output yang mengarah ke arah aktivitas sosial, yaitu pembiayaan (financing) ke usaha kecil (small business) dan dana sosial (social fund). Mereka melakukan pemilihan variabel untuk social efficiency tersebut dengan merujuk dan memodifikasi dari paper penelitian Widiarto & Emrouznejad (2015) dan (Gutierrez-Goiria, San-Jose, & Retolaza, 2016) yang meneliti tentang social efficiency pada lembaga keuangan Microfinance.…”
Section: Gambar 2 Proporsi Pemilihan Objek Penelitianunclassified
“…Several researches that have carried out applications for measuring efficiency in the Islamic banking industry in Indonesia can be found in research byHafez and Halim (2019); ; Rusydiana and Marlina (2019). Rusydiana and Sanrego (2018) have also conducted an analysis related to the framework for measuring the performance of Islamic banks in relation to the concept of efficiency.…”
Section: Tyas Rusydianamentioning
confidence: 99%
“…Based on the results of the analysis by Rusydiana and Marlina (2019), when viewed from the category of financial efficiency and social efficiency levels, Islamic banks that have high financial efficiency and social efficiency values consist of Bank Syariah Mandiri and BNI Syariah. Meanwhile, BRI Syariah is included in thequadrant with a low level of efficiency yet relatively high social efficiency.…”
Section: Tyas Rusydianamentioning
confidence: 99%
“…In the context of ASEAN Islamic banking, Nailah and Rusydiana (2020) recently investigated aspects of efficiency and stability using DEWA. Rusydiana and Marlina (2019) explored the financial and social efficiency of Indonesian Islamic banks using the DEA and Free Disposal Hull (FDH) methods. Previous studies have shown that topics related to efficiency, stability, and Islamic banking are still relevant.…”
Section: Related Literaturementioning
confidence: 99%